Caplacizumab Treatment for Acquired Thrombotic Thrombocytopenic Purpura - Marie Scully; Spero R. Cataland; Flora Peyvandi; Paul Coppo; Paul Knöbl; Johanna A. Kremer Hovinga; Ara Metjian; Javier de la Rubia; Katerina Pavenski; Filip Callewaert; Debjit Biswas; Hilde De Winter; et al. (2019)
In acquired thrombotic thrombocytopenic purpura (TTP), an immune-mediated deficiency of the von Willebrand factor–cleaving protease ADAMTS13 allows unrestrained adhesion of von Willebrand factor multimers to platelets and microthrombosis, which result in thrombocytopenia, hemolytic anemia, and tissue ischemia. Caplacizumab, an anti–von Willebrand factor humanized, bivalent variable-domain-only immunoglobulin fragment, inhibits interaction between von Willebrand factor multimers and platelets.